2023
DOI: 10.1111/ejh.14102
|View full text |Cite
|
Sign up to set email alerts
|

15‐color highly sensitive flow cytometry assay for post anti‐CD19 targeted therapy (anti‐CD19‐CAR‐T and blinatumomab) measurable residual disease assessment in B‐lymphoblastic leukemia/lymphoma: Real‐world applicability and challenges

Gaurav Chatterjee,
Priyanka Dhende,
Simpy Raj
et al.

Abstract: ObjectivesMeasurable residual disease (MRD) is the most relevant predictor of disease‐free survival in B‐cell acute lymphoblastic leukemia (B‐ALL). We aimed to establish a highly sensitive flow cytometry (MFC)‐based B‐ALL‐MRD (BMRD) assay for patients receiving anti‐CD19 immunotherapy with an alternate gating approach and to document the prevalence and immunophenotype of recurrently occurring low‐level mimics and confounding populations.MethodsWe standardized a 15‐color highly‐sensitive BMRD assay with an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Unfortunately, the cohort did not contain patients with CD19-negative MRD. Chatterjee et al [123] reported a 15-color panel using CD19, HLA-DR, CD22, and CD24 as B-cell markers, together with common maturation and aberrancy markers in combination with a gating strategy without use of CD19. This protocol allowed MRD assessment with a LOD of 0.0004% and LLOQ of 0.001% in patients with CD19-negative MRD when 5 × 10 6 cells are analyzed.…”
Section: Challenges and Novel Approaches For Flowcytometric Mrd Asses...mentioning
confidence: 99%
“…Unfortunately, the cohort did not contain patients with CD19-negative MRD. Chatterjee et al [123] reported a 15-color panel using CD19, HLA-DR, CD22, and CD24 as B-cell markers, together with common maturation and aberrancy markers in combination with a gating strategy without use of CD19. This protocol allowed MRD assessment with a LOD of 0.0004% and LLOQ of 0.001% in patients with CD19-negative MRD when 5 × 10 6 cells are analyzed.…”
Section: Challenges and Novel Approaches For Flowcytometric Mrd Asses...mentioning
confidence: 99%